INTERCULTURAL AND INTERFAITH: LITERATURE REVIEW ON MULTICULTURAL ISLAMIC EDUCATION IN INDONESIA - Handayani, Puspita; Asrohah, Hanun; Khoiriyah, Niswatin; Makhsun, Toha (Antis Publisher, 2024)
Intercultural and interfaith: literature review on multicultural Islamic education in Indonesia. The attitude of openness and dialogue between religions and cultures is a good concept to realize multicultural-based Islamic Education. Using the Systematic Literature Review method with the help of Nvivo 12 Plus to conduct a meta-analysis and lens.org application, it was found that the implementation of multicultural-based Islamic religious education carried out in Indonesia was still at the level of government policies listed in the law as well as teacher explanations in the classroom. This concept has not been included in the teaching text of Islamic Religious Education at all levels of education.